Correlation of Increased Serum Ferritin with SGOT, SGPT, and Albumin Levels in Children with β-Thalassemia Major - Cut Nanda Feby Ayulinda; Sulaiman Yusuf; Heru Noviat Herdata; Darnifayanti; Syafruddin Haris; Bakhtiar (Archives of Pediatric Gastroenterology, Hepatology, and Nutrition, 2022)
Background: Routine transfusion in β-thalassemia major children will cause excess iron in organs, especially the liver, as illustrated by the serum ferritin value. Excess iron in the liver can cause disturbances in liver enzymes and liver function, which can be assessed using SGOT, SGPT, and albumin examination parameters. This study intends to assess the relationship between increased serum ferritin levels with SGOT, SGPT, and albumin levels in β-thalassemia major children. Methods: This is an observational cross-sectional study which was conducted at the dr. Zainoel Abidin Hospital in Banda Aceh. Research subjects underwent examination of serum ferritin, SGOT, SGPT, and albumin. Results: A total of 37 β-thalassemia major children between 1 until <18 years of age were included in this study. The mean serum ferritin, SGOT, SGPT and albumin levels in β-thalassemia major patients were 4596 ± 2750.07 ng/mL, 57.32 ± 44.20 U/L, 57.46 ± 54.77 U/L, and 4.34 ± 0.22 g/dL respectively. The correlation coefficient between ferritin levels and SGOT was 0.768 (p-value <0.05). While, the correlation coefficient between ferritin and SGPT levels was 0.708 (p-value < 0.05). On the other hand, the correlation value between ferritin and albumin levels was -0.114 (p-value > 0.05). Conclusion: Increased serum ferritin levels in β-thalassemia major children are related to SGOT and SGPT levels. But there is no relationship between increased serum ferritin and albumin levels in β-thalassemia major children.